Thermodynamic and economic assessment of cyano functionalized anion based ionic liquid for CO2 removal from natural gas integrated with, single mixed refrigerant liquefaction process for clean energy. (15th January 2022) - Kazmi, Bilal; Haider, Junaid; Ammar Taqvi, Syed Ali; Qyyum, Muhammad Abdul; Ali, Syed Imran; Hussain Awan, Zahoor Ul; Lim, Hankwon; Naqvi, Muhammad; Naqvi, Salman Raza
Abstract: The study proposes a novel integrated process in which ionic liquid is utilized to control carbon dioxide (CO2 ) emissions from the natural gas combined with a single mixed refrigerant-based liquefaction process to assist safe transportation over long distances providing a sustainable and cleaner energy. Commercially amines are utilized for CO2 sequestration, but amines entail energy-intensive regeneration with elevated process costs. The present study offers a solvent screening mechanism based on important parameters such as heat of dissolution, viscosity, selectivity, working capacity, vapor pressure, corrosivity, and toxicity. The selected solvents' performance is computed by sensitivity analysis suggesting imidazolium-based cation 1-hexyl-3-methylimidazolium[Hmim] functionalized with tricyanomethanide(tcm) as anion a potential natural gas sweetening solvent in comparison with commercially used solvent monoethanoloamine(MEA), conventional ILs 1-butyl-3-methylimidazolium hexafluorophosphate [Bmim][Pf6 ] and 1-butyl-3-methylimidazolium methyl sulfate [Bmim][MeSO4 ]. The obtained sweet gas is liquefied using a single mixed refrigerant-based process providing 0.99 mol fraction of liquefied CH4 with less overall specific compression power requirement of 0.41 kW/kg of natural gas. Moreover, an exergy analysis demonstrates that the [Hmim][tcm] based process has lower total exergy destruction of 7.49 × 10 3  kW and is found to utilize less overall specific energy consumption 0.49 kWh/kg of NG in contrast to other studied solvents. Furthermore, a detailed economic analysis establishes [Hmim][tcm]-based CO2 integrated with liquefaction technology offers 50.7%, 74.4%, and 85.8% of total annualized cost (TAC) savings compared with the MEA-, [Bmim][Pf6 ]-, and [Bmim][MeSO4 ], respectively. Hence, [Hmim][tcm] for CO2 removal and integration with liquefaction process will incur unit cost based on the total annualized cost to be $2.2 × 10 4 /kmol of purified NG. Highlights: CO2 removal from natural gas integrated with single mixed refrigerant. Tricyanomethanide functionalized ionic liquid led to 99 wt% CH4 recovery. [Hmim][tcm]-based IL offers Specific thermal load of 0.43 kWh/kg natural gas. Unit cost for upgrading and liquefaction processes to be $ 2 × 10 4 /kmol of NG. $ 2.2 × 10 4 /kmol of purified NG rich in CH4 .